A new species of the genus Foenatopus Smith (Hymenoptera: Stephanoidea: Stephanidae) from India - Gupta, Ankita; Gawas, Sandesh M. (Zootaxa, 2020)
Foenatopus achterbergi sp. n., a new species of the stephanid genus, is described and illustrated from Karnataka, India. The new species is compared with all the possible closely allied species from the Oriental region.